Peran PAK Dewasa dalam Mempengaruhi Perilaku Konsumtif Generasi Milenial di Era Digital - Jemmy Susanto (Sekolah Tinggi Teologi Baptis Indonesia, 2026)
The digital era is characterized by the rapid development of technology, which has two sides, the side that provides benefits and the side that can harm. Changes in purchasing behavior are seen among millennials, a generation that grew up with the development of technology and communication. Their buying behavior is not just about fulfilling needs, tends to be excessive, not a priority scale, but motives, emotions, and challenges related to achieving happiness. Millennials are considered the most willing to spend money, especially when shopping online, and they prioritize short-term needs over long-term needs. The group is vulnerable to financial fraud in the practice of online loans with high-interest rates. Christian education plays a role in influencing the millennial generation through the Christian Awareness Triangle, self-awareness, vision awareness, and mission awareness, namely with an andragogic approach that presents solutions to the needs of the millennial generation by changing styles towards biblical truth. Abstrak Era digital ditandai perkembangan teknologi yang cepat, yang mempunyai dua sisi, sisi yang memberi manfaat dan sisi yang merugikan. Perubahan perilaku pembelian terlihat di kalangan milenial, generasi yang tumbuh dengan perkembagan teknologi dan komunikasi. Perilaku pembeliaannya bukan sekedar pemenuhan kebutuhan, cenderung berlebihan, bukan skala prioritas, melainkan motif, emosi, tantangan yang berkaitan dengan pencapaian kebahagiaan. Milenial dianggap paling rela mengeluarkan uang, terutama saat berbelanja online, dan mereka memprioritaskan kebutuhan jangka pendek daripada kebutuhan jangka panjang. Kelompok rentan terhadap penipuan keuangan dalam praktek pinjaman online dengan bunga tinggi. Pendidikan Kristen berperan dalam mempengaruhi generasi milenial melalui Christian Awareness Triangle, kesadaran diri, kesadaran visi dan kesadaran misi yaitu dengan pendekatan andragogik yang menghadirkan solusi atas kebutuhan generasi milenial dengan mengubah gaya menuju kebenaran Alkitab.